Great by choice [compact disc, unabridged] : uncertainty, chaos, and luck : why some thrive despite them all - Collins, James C. (James Charles), 1958- (Harper Audio, 2011)
Enumerates the principles for building a truly great enterprise in unpredictable, tumultuous and fast-moving times.